Pernikahan Anak Kabupaten Sinjai Ditinjau Dalam Perspektif Teori Pertukaran George Homans (Equilibrium: Jurnal Pendidikan, 2025)
This study aims to analyze the phenomenon of child marriage in Sinjai Regency through the perspective of George Homans' exchange theory. This theory is used to understand how individuals and families make marriage decisions based on considerations of value and cost. The method employed in this research is a qualitative approach with in-depth interviews and participatory observation techniques, involving informants who are couples married under the age of 19, as well as their parents from various social and economic backgrounds. The results indicate that child marriage in Sinjai Regency is caused by three main factors: economic reasons, arranged marriages, and premarital pregnancies. The economic factor serves as the primary driver, where families view marriage as a solution to financial difficulties and a means to enhance social status. Arranged marriages, often influenced by cultural norms, also contribute to the decision to marry. Additionally, premarital pregnancies create social pressure that encourages individuals to marry as a form of responsibility. These findings reflect the fundamental principles of Homans' exchange theory, where individuals strive to maximize benefits and minimize losses in social interactions. Therefore, it is essential for the government and society to raise awareness of the negative impacts of child marriage and provide better alternatives, such as education and economic empowerment programs, to reduce the incidence of child marriage in Sinjai Regency.